Genotyping by sequencing provides new insights into the diversity of Napier grass (Cenchrus purpureus) and reveals variation in genome-wide LD patterns between collections - Muktar, Meki S.; Teshome, A.; Hanson, Jean; Negawo, Alemayehu T.; Habte, Ermias; Domelevo Entfellner, Jean-Baka; Ki-Won Lee; Jones, Christopher S. (Springer, 2019)
Napier grass is an important tropical forage-grass and of growing potential as an energy crop. One-hundred-five Napier grass accessions, encompassing two independent collections, were subjected to genotyping by sequencing which generated a set of high-density genome-wide markers together with short sequence reads. The reads, averaging 54 nucleotides, were mapped to the pearl millet genome and the closest genes and annotation information were used to select candidate genes linked to key forage traits. 980 highly polymorphic SNP markers, distributed across the genome, were used to assess population structure and diversity with seven-subgroups identified. A few representative accessions were selected with the objective of distributing subsets of a manageable size for further evaluation. Genome-wide linkage disequilibrium (LD) analyses revealed a fast LD-decay, on average 2.54 kbp, in the combined population with a slower LD-decay in the ILRI collection compared with the EMBRAPA collection, the significance of which is discussed. This initiative generated high-density markers with a good distribution across the genome. The diversity analysis revealed the existence of a substantial amount of variation in the ILRI collection and identified some unique materials from the EMBRAPA collection, demonstrating the potential of the overall population for further genetic and marker-trait-association studies.